Good Corporate Image, Good Taxpayer? An Investigation Of The Impact Of Corporate Reputation On Tax Compliance Behavior - Purwiyanti, Deviana Wahyu; Laksito, Herry (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2025)
This study aims to examine the effect of corporate reputation on taxpayer compliance, with company size as a moderating variable. Using the Moderated Regression Analysis (MRA) method, this study focuses on companies named as recipients of the Most Tax-Friendly Corporate Country Contributor Award in 2020. These companies were selected for their reputation for good tax compliance. This study covers the period from 2020 to 2024, with the aim of exploring how corporate reputation affects tax compliance, as well as how company size can strengthen this influence. The results show that corporate reputation has a positive and significant influence on taxpayer compliance. Furthermore, company size is proven to strengthen the relationship between reputation and tax compliance. These findings provide new insights for tax policy and company managers to pay more attention to company reputation and size in an effort to improve tax compliance.